Short‐term morbidity and types of intrapartum hypoxia in the newborn with metabolic acidaemia: a retrospective cohort study. (22nd March 2022) - di Pasquo, Elvira; Commare, Arianna; Masturzo, Bianca; Paolucci, Sonia; Cromi, Antonella; Montersino, Benedetta; Germano, Chiara M.; Attini, Rossella; Perrone, Serafina; Pisani, Francesco; Dall'Asta, Andrea; Fieni, Stefania; et al.
Abstract: Objectives: To assess labour characteristics in relation to the occurrence of Composite Adverse neonatal Outcome (CAO) within a cohort of fetuses with metabolic acidaemia. Design: Retrospective cohort study. Setting: Three Italian tertiary maternity units. Population: 431 neonates born with acidaemia ≥36 weeks. Methods: Intrapartum CTG traces were assigned to one of these four types of labour hypoxia: acute, subacute, gradually evolving and chronic hypoxia. The presence of CAO was defined by the occurrence of at least one of the following: Sarnat Score grade ≥2, seizures, hypothermia and death <7 days from birth. Main outcome measures: To compare the type of hypoxia on the intrapartum CTG traces among the acidaemic neonates with and without CAO. Results: The occurrence of a CAO was recorded in 15.1% of neonates. At logistic regression analysis, the duration of the hypoxia was the only parameter associated with CAO in the case of an acute or subacute pattern (odds ratio [OR] 1.3; 95% CI 1.02–1.6 and OR 1.04; 95% CI 1.0–1.1, respectively), whereas both the duration of the hypoxic insult and the time from PROM to delivery were associated with CAO in those with a gradually evolving pattern (OR 1.13; 95% CI 1.01–1.3 and OR 1.04; 95% CI 1.0–1.7, respectively). The incidence of CAO was higher in fetuses with chronic antepartum hypoxia than in those showing CTG features of intrapartum hypoxia (64.7 vs. 13.0%; P  < 0.001). Conclusions: The frequency of CAO seems related to the duration and the type of the hypoxic injury, being higher in fetuses showing CTG features of antepartum chronic hypoxia. Tweetable abstract: This study demonstrates that in a large population of neonates with metabolic acidaemia at birth, the overall incidence of short‐term adverse outcome is around 15%. Such risk seems closely correlated to the duration and the type of hypoxic injury, being higher in fetuses admitted in labour with antepartum chronic hypoxia than those experiencing intrapartum hypoxia. Tweetable abstract: This study demonstrates that in a large population of neonates with metabolic acidaemia at birth, the overall incidence of short‐term adverse outcome is around 15%. Such risk seems closely correlated to the duration and the type of hypoxic injury, being higher in fetuses admitted in labour with antepartum chronic hypoxia than those experiencing intrapartum hypoxia.